Neuronal protective effect of Songling Xuemaikang capsules alone and in combination with carbamazepine on epilepsy in kainic acid-kindled rats - Haiyan Yang; Rui Zhang; Chen Jia; Mengyu Chen; Wen Yin; Liming Wei; Haisheng Jiao (Taylor & Francis Group, 2019)
Context: Epilepsy is a common life-threatening neurological disorder that is often drug-resistant and associated with cognitive impairment. The traditional Chinese patent medicine Songling Xuemaikang capsules (SXC) is clinically used for epilepsy therapy and alleviation of cognitive impairment. Objective: This study investigates the neuronal protective effect of SXC combined with carbamazepine (CBZ) on epilepsy and cognitive impairment in kainic acid-kindled SD rats. Materials and methods: Kainic acid-kindled rats were established by injection of 0.45 μg kainic acid and randomly divided into 5 groups (n = 14): saline (sham-operated), control, CBZ, SXC and CBZ + SXC combined group. Rats in the treatment groups received CBZ (50 mg/kg/d), SXC (600 mg/kg/d) or combined CBZ (50 mg/kg/d) + SXC (600 mg/kg/d) via intragastric injection for 60 days. Epileptic behaviours, cognitive impairment, neuronal apoptosis and expression of p-Akt, Akt and caspase-9 were measured, and the alleviation of cognitive damage and neuronal apoptosis was analyzed. Results: The combined administration of SXC and CBZ significantly decreased the frequency of seizures (1.2 ± 0.3) and the number of episodes (1.3 ± 0.5) above stage III (p < 0.05). Neuronal apoptosis was improved (p < 0.01), and cognitive damage was ameliorated (p < 0.05).The level of p-Akt was enhanced (p < 0.01) whereas the expression of caspase-9 was evidently inhibited (p < 0.01) in the combined group. Conclusions: The present findings confirm that the combined use of SXC with CBZ can effectively control epileptic seizures, alleviate damage to hippocampal neurons and protect against cognitive impairment. The mechanism of action might be related to the upregulation of p-Akt and inhibition of caspase-9 expression.